Bichromophoric compounds with orthogonally and parallelly arranged chromophores separated by rigid spacers - Meineke, Dirk; Hell, Stefan (Chemistry - a European journal, 2017)
Electronic energy transfer (EET) between chromophores is of fundamental importance for many biological processes and optoelectronic devices. However, common models fall short in fully describing the process, especially in bichromophoric model systems with a donor and acceptor connected by a rigid linker providing perpendicular geometries. Herein, we report a novel strategy for preparing bichromophores containing adamantane or 2-(2-adamantylidene)adamantane as rigid spacers, providing a fixed distance between chromophores, and their parallel or perpendicular arrangement without chromophore rotation. New fluorophores were developed and linked via spiroatoms. Bichromophores with identical (blue-blue) or different (blue-red) chromophores were synthesized, either in orthogonal or parallel geometry. These were characterized by absorption/fluorescence spectroscopy, time-resolved fluorescence anisotropy, and fluorescence antibunching measurements. Based on the Förster point-dipole approximation, EET efficiencies were estimated by using geometrical parameters from (time-dependent) density functional calculations. For bichromophores with parallel geometry, the predicted EET efficiencies were near unity and fit the measurements. In spite of estimated values around 0.4 and 0.5, 100 % efficiency was observed also for bichromophores with orthogonal geometry. The new rigid scaffolds presented here open new possibilities for the synthesis of bichormophores with well-defined parallel or perpendicular geometry.